Can we improve obstetric outcomes in type 1 diabetic pregnancy?. (18th April 2012) - Pearson, L; Maresh, MJA
Abstract : The 2002-3 national survey of diabetic pregnancy (CEMACH)1 confirmed the continued poor outcomes in diabetic pregnancy. Pregnancies in a consecutive cohort of 197 type 1 diabetic women who reached the second trimester between 1998-2010 were studied. They were managed by the same team in an individualised manner using standard protocols and their outcomes compared to CEMACH data. Factors reflecting pre-pregnancy care such as pre-conception counselling, use of folic acid and early HbA1c values did not differ significantly from CEMACH. Deprivation was significantly more common with 48% in the most deprived quintile compared to 22% in CEMACH. Despite this the median gestation at first assessment was 56 days. However there was a higher rate of congenital malformations than in CEMACH (86/1000 v. 48/1000, p<0.03) which did not appear to relate to deprivation, but more to lack of pre-pregnancy care. There were 2 ante-partum stillbirths at 26 and 37 weeks (10/1000) compared to CEMACH (26/1000). The caesarean section rate was less than CEMACH (52% v. 67% p<0.0001). There was a trend towards less preterm deliveries in our cohort (31% v. 37%). Significantly less babies in our cohort had birthweights >90 th centile (41% v 52%, p<0.005) and less babies in our cohort were separated from their mothers by admission to special care units (39% v 51%, p<0.0001) In conclusion it appears that centralisation of care of type 1 diabetic pregnancy to larger units able to individualise care may be associated with more normal obstetric outcomes; however pre-pregnancy preparation remains a major issue. Confidential Enquiry into Maternal and Child Health.